Pengembangan Perangkat Pembelajaran Team Based Learning- Pbl Berbantuan WhatsApp dan Facebook Messenger - Supartin, Supartin; Galanggadjir, Triska Laurensya; Arbie, Asri (Jurnal Riset Fisika Edukasi dan Sains, 2021)
The Covid 19 pandemic has a major impact on all sectors of life including in the world of education. The implementation of PJJ (Distance Learning) requires new innovations in the development of learning devices so that learning continues to run well even though learning activities are carried out at home. The development model used in this research is the 4D Development model. The result of this study is that the learning device is said to be "valid" through a construct validity test. The resulting learning device is said to be practical based on the average percentage of learning implementation during 3 meetings by 95% and the percentage of teacher and learners' response results related to the use of learning devices in the online learning process by 98%-100% and 82%-86% on indicators. Concluded learning devices are developed quality and can be used as a new reference in the learning process.Keywords: Team Based Learning, Problem Based Learning (PBL), Learning Tools